Two new relict Syncordulia species found during museum and field studies of threatened dragonflies in the Cape Floristic Region (Odonata: Corduliidae) - Dijkstra, Klaas-Douwe B.; Samways, Michael J.; Simaika, John P. (Zootaxa, 2007)
Red List assessments often require the verification of records and taxonomy in museum collections and the field. Such research during an assessment of threatened dragonflies in the Cape Floristic Region (CFR) biodiversity hotspot, led to the discovery of two new narrow-range endemic Syncordulia species, bringing the known total to four in the genus. The new species, Syncordulia legator and S. serendipator, are described with emphasis on their identification, ecology and biogeography. Morphological diversity within the genus and the absence of obvious close relatives suggest an ancient and isolated presence in the CFR, emphasizing the uniqueness and conservation importance of the region’s endemic odonate fauna.